A novel gut microbiome therapeutic derived from dietary polyphenols attenuates neuroinflammation in vivo in a model of c9orf72 mediated frontotemporal dementia: Nonhuman/Target identification and validation studies: Inflammation and innate immunity. (7th December 2020) - Trageser, Kyle J.; Smith, Chad; Estill, Molly; Sebastian, Maria; Pasinetti, Giulio Maria
Abstract: Background: Frontotemporal dementia (FTD) is a neurodegenerative disorder with various genetic etiologies, the most prevalent of which include G4 C2 expansions in the c9orf72 gene. Expansions produce dipeptide repeat proteins (DPR), forming aggregates with deleterious impacts on cellular processes and correlating with neuroinflammation. Glycine‐Arginine (GR) aggregates are the only significantly correlated DPR found in clinically relevant neuroanatomical regions of the brain. Our current study investigates the contribution of innate immunity to FTD pathogenesis and the attenuation of neuropathologies with the brain bioavailable microbiome‐derived metabolite, 3‐hydroxybenzoic acid (3‐HBA). Method: Mice were transfected via intracerebroventricular injection with AAV9‐GFP(GR)100 or AAV9‐GFP and treated starting on Day 28 with either PBS vehicle or 50 mg kg ‐1 of 3‐HBA. At 14 weeks mice were sacrificed and frontal cortex (FC), somatosensory cortex (CTX), and hippocampal (HP) tissue was dissected and prepared for RNA sequencing. Differentially expressed genes (DEGs) were identified using DESeq2 and pathway alterations were detected using Ingenuity Pathway Analysis. ELISA for IL‐1β was conducted on FC, CTX, and HP tissue. To determine the ability of 3‐HBA to reduce secretion of IL‐1β, primary microglia pretreated with 3‐HBA were stimulated with LPS+ATP and IL‐1β concentration was analyzed by ELISA. Result: DEGs associated with FTD pathology, protein expression levels of the pro‐inflammatory cytokine IL‐1β, and subsequent amelioration via treatment with 3‐HBA were demonstrated to be a result of contributions from the innate immune system and inflammasome activation in microglia. Inflammatory pathways differentially enriched among treatment groups include TREM1 Signaling, the complement system, and NFκB signaling. GR‐100 Vehicle treated animals exhibited elevated IL‐β in cortical tissue. 3‐HBA was efficacious in vivo in rescuing IL‐1β levels in GR‐100 HBA treated mice to levels of GFP animals. Primary microglia pretreated with 3‐HBA and stimulated with LPS+ATP significantly reduced IL‐1β release, signifying the efficacy of 3‐HBA in attenuating innate immune reactivity. Conclusion: Pathways and genes associated with the innate immune system show enrichment in a model of FTD and are rescued by administration of 3‐HBA. Overexpression of IL‐1β in the cortex of GR‐100 Vehicle animals is attenuated by the administration of 3‐HBA. Our data implicates a gut‐brain axis mechanism of treatment for key FTD associated neuropathologies.